lncRNA PRADX is a Mesenchymal Glioblastoma Biomarker for Cellular Metabolism Targeted Therapy - Xu, Can; Zhao, Jixing; Song, Jia; Xiao, Menglin; Cui, Xiaoteng; Xin, Lei; Xu, Jianglong; Zhang, Yuhao; Yi, Kaikai; Hong, Biao; Tong, Fei; Tian, Shaohui; et al. (Frontiers in Oncology, 2022)
Glioblastoma (GBM) is the most common and lethal type of primary malignant central nervous system (CNS) tumor with an extremely poor prognosis, and mesenchymal subtype of GBM has the worst prognosis. Here, we found that lncRNA PRADX was overexpressed in the mesenchymal GBM and was transcriptionally regulated by RUNX1-CBFβ complex, overexpressed PRADX suppressed BLCAP expression via interacting with EZH2 and catalyzing trimethylation of lysine 27 on histone H3 (H3K27me3). Moreover, we showed that BLCAP non-functionally interacted with STAT3, overexpressed PRADX activated STAT3 phosphorylation, and promoted ACSL1 expression via suppressing BLCAP expression, accelerating tumor metabolism. Finally, we determined that the combined use of ACSL1 and CPT1 inhibitors could reverse the accelerated cellular metabolism and tumor growth induced by PRADX overexpression in vivo and in vitro. Collectively, PRADX/PRC2 complex activated STAT3 pathway and energy metabolism in relation to mesenchymal GBM progression. Furthermore, our findings provided a novel therapeutic strategy targeting the energy metabolism activity of GBM.